2012
DOI: 10.3389/fendo.2012.00171
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide W

Abstract: Neuropeptide W (NPW), which was first isolated from the porcine hypothalamus, exists in two forms, consisting of 23 (NPW23) or 30 (NPW30) amino acids. These neuropeptides bind to one of two NPW receptors, either NPBWR1 (otherwise known as GPR7) or NPBWR2 (GPR8), which belong to the G protein-coupled receptor family. GPR7 is expressed in the brain and peripheral organs of both humans and rodents, whereas GPR8 is not found in rodents. GPR7 mRNA in rodents is widely expressed in several hypothalamic regions, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Both of them are produced from a common precursor peptide, prepro-NPW by proteolytic cleavage of two pairs of arginine residues at position 24–25 and 31—2 ( Takenoya et al, 2010a ). The name of NPW is derived from tryptophan residues (single-letter code W) as it appears in both the terminal N- and C- in its two mature forms ( Takenoya et al, 2012 ). Abundance of both these isoforms were demonstrated in several species including human, rat, mouse, pig, and chicken ( Brezillon et al, 2003 ; Tanaka et al, 2003 ; Kitamura et al, 2006 ; Fang et al, 2015 ; Bu et al, 2016 ).…”
Section: Structurementioning
confidence: 99%
“…Both of them are produced from a common precursor peptide, prepro-NPW by proteolytic cleavage of two pairs of arginine residues at position 24–25 and 31—2 ( Takenoya et al, 2010a ). The name of NPW is derived from tryptophan residues (single-letter code W) as it appears in both the terminal N- and C- in its two mature forms ( Takenoya et al, 2012 ). Abundance of both these isoforms were demonstrated in several species including human, rat, mouse, pig, and chicken ( Brezillon et al, 2003 ; Tanaka et al, 2003 ; Kitamura et al, 2006 ; Fang et al, 2015 ; Bu et al, 2016 ).…”
Section: Structurementioning
confidence: 99%
“…These findings are similar to those reported by Takenoya et al (2010b), who demonstrated the presence of NPW-ir fibers in the POA, BST, amygdala, PVN, ARC, VMH, LH, and PAG. Previous studies have established the LH as a feeding center, the VMH as the satiety center, and the ARC as the integrated center for feeding regulation (Takenoya et al, 2010a(Takenoya et al, , 2010b(Takenoya et al, , 2012. Levine et al (2005) demonstrated that injection of NPW23 into the PVN and LH caused an increase in food intake.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that appetite is regulated by many neuropeptides, and that takes place via a neural network linking these brain centers. Neuropeptide Y (NPY), melanin-concentrating hormone (MCH), orexin, galanin, and agouti gene-related protein (AgRP) are typical orexigenic peptides, while α-melanocyte stimulating hormone (α-MSH), corticotropin-releasing hormone (CRH), cocaine-and amphetamine-regulated transcript (CART), neuropeptide W (NPW) and galanin-like peptide (GALP) have been described as anorexigenic peptides [7][8][9][10][11][12][13][14]. Moreover, the levels of many neuropeptides are linked to the actions of leptin, in addition to which it has been shown that neurons containing feeding regulating neuropeptides interact with each other via synaptic inputs [15,16].…”
Section: Introductionmentioning
confidence: 99%